Mix design for self-compacting palm oil clinker concrete based on particle packing - Kanadasan, Jegathish; Razak, Hashim Abdul (Elsevier, 2014)
The consumption of waste materials in self-compacting concrete (SCC) in the construction industry will not only help to conserve the natural resources but also promote sustainability in preserving the environment. Palm oil clinker (POC) is a waste by-product from the incineration process of oil palm shells and fibres. They are porous and lightweight in nature, which makes them suitable for use as a lightweight aggregate (LWA). In this study, a new procedure was employed to obtain the mix design based on the particle packing (PP) concept to ensure the fresh and hardened properties of SCC are achieved. The actual packing level of aggregate and paste volume is integrated into the proportioning method to obtain the final mix design. The proposed procedure was verified by evaluating the SCC formed for self-compactability and mechanical properties. Based on the overall performance of fresh and hardened properties, it can be deduced that the procedure satisfied the requirements for SCC. The satisfactory results indicate that the mix design can be employed not only for POC but also for a variety of combinations of aggregate. Â© 2013 Elsevier Ltd.